Influences of mental accounting on consumption decisions: asymmetric effect of a scarcity mindset - Cheng, Lin; Yu, Yinqiang; Wang, Yizhi; Zheng, Lei (Frontiers in Psychology, 2023)
A scarcity mindset is considered to impact consumer behaviors. Our research aimed to examine the moderating effect of the scarcity mindset on the relationship between mental accounting and hedonic (vs. utilitarian) consumption. We conducted an online experimental design (mental accounting: windfall gains vs. hard-earning gains; consumption: hedonic products vs. utilitarian products) and verified our hypotheses in two distinct samples: a student sample and an adult sample. Our results showed that consumers who received windfall gains tended to use it for hedonic consumption rather than utilitarian consumption. Intriguingly, such an effect was insignificant under a high level of a scarcity mindset but significant under a low level of the scarcity mindset. Moreover, consumers who received hard-earning gains tended to spend the money on utilitarian (vs. hedonic) consumption. However, we did not detect the impact of the scarcity mindset on such effects. Our research suggested an asymmetric effect of the scarcity mindset on hedonic (vs. utilitarian) consumption under two different mental accounts. It highlights the important role of the scarcity mindset in consumer behaviors, which leaves avenues for future research to understand marketing promotion strategies for distinct products.